2002
DOI: 10.1002/em.10088
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity of naturally occurring indole compounds: correlation between covalent DNA binding and other genotoxicity tests

Abstract: 3-Methylindole (3MI), melatonin (Mel), serotonin (Ser), and tryptamine (Tryp) were evaluated in vitro for their potential to induce DNA adducts, DNA strand breaks, chromosomal aberrations (Abs), inhibition of DNA synthesis, and mutations. All compounds produced DNA adducts in calf thymus DNA in the presence of rat liver S9. In cultured rat hepatocytes, all produced DNA adducts but none induced DNA strand breaks. In Chinese hamster ovary cells, 3MI and Mel produced DNA adducts, Abs, and inhibition of DNA synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 60 publications
1
24
0
Order By: Relevance
“…This reactivity has been studied primarily for isothiocyanates. They can undergo addition as well as substitution reactions with nucleophiles [1,3,26,27]. Substitution reactions have been observed primarily with benzylic isothiocyanates, a class that includes indolylmethyl isothiocyanates.…”
Section: Laboratory a (Research Centre For Industrialmentioning
confidence: 98%
“…This reactivity has been studied primarily for isothiocyanates. They can undergo addition as well as substitution reactions with nucleophiles [1,3,26,27]. Substitution reactions have been observed primarily with benzylic isothiocyanates, a class that includes indolylmethyl isothiocyanates.…”
Section: Laboratory a (Research Centre For Industrialmentioning
confidence: 98%
“…(Florin et al, 1980) Ames assay S. typhimurium TA98; TA100 Not reported Negative 3 (Kim et al, 1989) Ames assay (preincubation method) (Reddy et al, 2002) Aberrations were only detected at cytotoxic concentrations that (Florin et al, 1980) Single dose study.…”
Section: S Typhimurium Tm677mentioning
confidence: 99%
“…( (Ochiai et al, 1986) S. typhimurium TA100 Up to 3.33 mM (437 µg/ml) Negative 3 (Reddy et al, 2002) Mutation assay (paper-disk method)…”
Section: S Typhimurium Tm677mentioning
confidence: 99%
“…Chinese hamster ovary cells 1.3, 1.4 and 1.5 mM (+ S9) 1.4, 1.5 and 1.6 mM (-S9) Positive 1 (Reddy et al, 2002) Aberrations were only detected at cytotoxic concentrations that showed marked inhibition of DNA (Florin et al, 1980) Single dose study.…”
Section: S Typhimurium Tm677mentioning
confidence: 99%